Iranian women's attitude toward childbearing and its' association with generalized trust, social support, marital satisfaction and governmental childbearing incentives - Mehran Alijanzadeh; Nasim Bahrami; Elahe Jafari; Mohsen Noori; Fatemeh Miri; Mahsa Joftyar; Mark D. Griffiths; Zainab Alimoradi (Heliyon, 2023)
Background: Having a child is important event for families worldwide. Attitudes toward childbearing are influenced by many factors. The aim of the present study was to investigate Iranian women's attitude toward childbearing and its association with generalized trust, social support, marital satisfaction, mental health, and socio-economic characteristics in Qazvin province. Methods: A cross-sectional survey study was conducted between April and July 2022. Using convenience sampling, 347 women with no children or one child in Qazvin province (Iran) participated in the study. Data were collected via the Iranian online platform Porsline. The survey included a demographic and fertility characteristics questionnaire, Attitudes Toward the Government's Childbearing Incentives Scale (ATGCIS), Attitudes Toward Fertility and Childbearing Scale (ATFCS), ENRICH Marital Satisfaction Scale (ENRICH MSS), Patient Health Questionnaire (PHQ-4), Multidimensional Scale of Perceived Social Support (MSPSS), and Generalized Trust Scale (GTS). Findings: The average age of participants was 35.66 years (SD = 6.89). The score of attitudes toward fertility and childbearing was 84.66 out of 134 (SD = 19.17). The average number of expected children by the couple was 2.36 (SD = 1.35). Multivariable linear regression found a positive and significant relationship between participants' attitudes toward fertility and childbearing (ATFC) and (i) governmental childbearing incentives (β = 0.365, p < 0.001, with 1.37 increase in ATFC with each unit increase in this scale) (ii) generalized trust (i.e., individual's expectation of others' trustworthiness), (β = 0.155, p < 0.003, with 0.60 increase in ATFC with each unit increase in generalized trust) and (iii) marital satisfaction (β = 0.146, p < 0.005, with 0.26 increase in ATFC with each unit increase marital satisfaction). The multivariable linear regression model also showed that attitudes toward fertility and childbearing was the only predictor of couples' expected number of children in the future (β = 0.214, p < 0.001, with 0.38 increase in couples' expected number of children with each unit increase in ATFC). Conclusion: Government incentives were the strongest independent predictor of participants' attitudes toward childbearing which can indirectly influence couples' expected number of children in the future. Consequently, governments may be able to influence couples' childbearing decisions by providing appropriate incentives. Generalized trust and marital satisfaction were other significant predictors of attitudes toward childbearing. Therefore, implementing programs to improve generalized trust, and increasing marital satisfaction might be other influential measures in couples’ childbearing decisions.